Effect of mitophagy in the formation of osteomorphs derived from osteoclasts - Tingben Huang; Yuchen Wang; Zhou Yu; Xiaoyan Miao; Zhiwei Jiang; Ke Yu; Mengdie Fu; Kaichen Lai; Ying Wang; Guoli Yang (iScience, 2023)
Summary: Osteoclasts are specialized multinucleated giant cells with unique bone-destroying capacities. A recent study revealed that osteoclasts undergo an alternative cell fate by dividing into daughter cells called osteomorphs. To date, no studies have focused on the mechanisms of osteoclast fission. In this study, we analyzed the alternative cell fate process in vitro and, herein, reported the high expression of mitophagy-related proteins during osteoclast fission. Mitophagy was further confirmed by the colocalization of mitochondria with lysosomes, as observed in fluorescence images and transmission electron microscopy. We investigated the role played by mitophagy in osteoclast fission via drug stimulation experiments. The results showed that mitophagy promoted osteoclast division, and inhibition of mitophagy induced osteoclast apoptosis. In summary, this study reveals the role played by mitophagy as the decisive link in osteoclasts’ fate, providing a new therapeutic target and perspective for the clinical treatment of osteoclast-related diseases.